Keselarasan Hukum Islam dengan Hukum Nasional dalam Perspektif Penyelesaian Tindak Pidana Zina di Indonesia - aisyah, Aisyah Cinta Putri Wibawa; ashza, Ashza Nur Siam; Tuhfah Humairah Mufidah; Asep Sopian (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2023)
Indonesia is a constitutional state, where all forms of irregularities have been regulated in order to achieve harmony in human life. In the national legal system there are three elements that play a role, namely customary law, Islamic law and western law. However, are the perspectives of each legal category aligned? This article discusses the perspective of Islamic law and national law in the settlement of adultery crimes using qualitative research methods and approaches to literature studies and interviews. The results of the study show that there are differences regarding the terms and sanctions for adulterers. In Article 284 of the Criminal Code, the perpetrators of adultery who are bound by legal marriage ties only carry a maximum penalty of nine months in prison. Meanwhile, from the perspective of Islamic law, any intercourse between a woman and a man without a valid marriage bond is said to be adultery with two categories of punishments given, namely muhsan adultery where the adulteress is married, the punishment is stoning or stoned to death and adultery ghairu muhsan where the adulteress is never been married, the penalty is binding (100 lashes) and if still alive, then must be exiled to a secluded blood for one year.